Pendampingan Pengelolaan Desa Wisata Watugede Untuk Meningkatkan Kesejahteraan Masyarakat - M Soleh Mauludin; Khurun’in; Saidul Hafizi; Muhammad Bayu Fikrul Khoir; Tia Nurhidayah; Hana Mariska Dewi; Chumidatus Sa'diyah; Nilna Fatikhatul Husna; Alfinafristi Damayanti; Saila Rizka Kamila (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
One strategy to improve community welfare is to develop MSMEs and utilize various media, both digital and print, as promotional tools. MSMEs have a major contribution to the local economy, especially in Watugede Village which has natural resource potential, such as the Watugede Raya Embung. This research uses the Asset-Based Community Development (ABCD) approach, which places the community as the main actor in managing village potential. The "Fishing Mania Embung Watugede Raya" activity is a form of active community involvement in local economic development, resulting in increased income from the parking sector and MSME sales managed by PKK women and BUMDes. The research results show that people's welfare does not only depend on economic aspects, but also the overall quality of life. Promotion through the media, including interviews on Radio Republik Indonesia, has proven effective in increasing the number of visitors. Thus, community-based natural resource management can contribute to sustainable village economic development.